Lénine et la 3ème internationale. - Lazitch, Branko; Aron, Raymond (Paris : Ed. de la baconnière, 1951)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: Derde Internationale (1919-1943).; Lenin, Vladimir Iljitsj